“The Noble Nest” of I. S. Turgenev in Assessing Translator Lei Ran: on the Issue of the Novel Reception in China - Y. Chen; I. A. Belyaeva (Научный диалог)
In the framework of the general question about the perception of Turgenev’s novel “The Noble Nest” in China, in the article the assessments of this work were examined, which were proposed by the famous Chinese translator and connoisseur of Russian culture Lei Ran. The novelty of the research lies in the fact that the article for the first time analyzes the position of the translator, which is different in depth and represents a systematic assessment of the novel. The strengths of Lei Ran’s reception of “The Noble Nest” are connected with the translator’s observations on the poetics of this work (plot structure, contrasts and comparisons, psychologism, brevity, lyricism, etc.), as well with her reflections on the problems of interaction between western sentiments and national ideas. Lei Ran’s assessments of religiosity of the main female character and religious beliefs that in general distinguish Russian culture seem controversial. The translator sees in them the objective and subjective conditionality of the tragic outcome of the personal history of the main characters in Turgenev’s novel. This generally corresponds to the nature of the perception of these issues by the Chinese society, but hardly reflects the Russian realities. Interpretation of the novel “The Noble Nest”, proposed by Lei Ran, is estimated in the article as an important stage of the Chinese “turgeniana”.